XPS, structural and antimicrobial studies of novel functionalized halloysite nanotubes - Rashad Al-Gaashani (16936965) (2022)
A novel robust preparation method based on thermal salt decomposition has been elaborated for synthesis of halloysite nanotubes (HNTs) impregnated with silver and iron oxide nanoparticles. The developed method is simple, time-effective, and can be employed for large scale material fabrication. Different characterization techniques, including X-ray diffraction (XRD), scanning and transmission electron spectroscopy (SEM and TEM) and energy dispersive X-ray spectroscopy (EDS) have been used to characterize the functionalized HNTs composite materials. Surface elemental and chemical state analysis was conducted using X-ray photoelectron spectrometer (XPS). The functionalized HNTs exhibit enhanced total surface area (by 17.5%) and pore volume (by 11%) compare to the raw HNTs calculated by using the Brunauer–Emmett–Teller (BET) method. It was shown that functionalized HNTs possess high antimicrobial properties towards both gram- positive and gram-negative bacteria species. The enhanced surface area and bactericidal properties of functionalized HNTs could be beneficial for employing of the prepared material as low cost filtration media for water treatment applications. Molecular dynamics (FPMD) were performed to obtain insights about possible physiochemical mechanisms for chemical adsorption and on the HNT thermal stability. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-022-25270-7